Implementation of Pollution Control Measures on Littering in Dela Costa Homes V (DLCHV), Barangay Burgos, Rodriguez, Rizal, Philippines - Bancifra, Jeffrey (PT. Riset Press International, 2025)
The Dela Costa Homes V subdivision consists of 2,400 housing units. The housing units are built as row houses, each with a minimum lot size of 50 sq. m. The subdivision's Home Owners Association (HOA) coordinates with the Local Government Unit (LGU) of Barangay Burgos. The study is descriptive quantitative research that assessed the efficiency of implementing pollution control measures on littering in the research locale. The data was gathered through a Resident Assessment Survey (RAS) incorporating Waste Management Theory and Environmental Scanning through PESTEL Analysis. Random sampling was used to collect data from one hundred residents (one respondent per household). The residents commented about their experiences and wrote suggestions relative to the control measures on littering. Using Analysis of Variance (ANOVA) and Independent t-test, it is found that there is no significant difference in the efficiency of Pollution Control Measures on Littering in terms of Political, Economic, Technological, Environmental, and Legal Aspects. On the other hand, there is a significant difference in the responses of unit owners and renting occupants concerning Socio-Cultural Aspect. Respondents gave a 'Slightly Efficient' rating to the Political, Economic, Socio-Cultural, Technological and Environmental control measures. Furthermore, results show that Pollution Control Measures on Littering are not that evident for most of the residents of DLCHV either because of unawareness or lack of implementation. As for the Legal aspect, this needs the most improvement due to its 'Not Efficient at All' rating.